Education and Economic Growth in Post-apartheid South Africa: An Autoregressive Distributive Lag Approach - Malangeni, Luxolo; Phiri, Andrew (International Journal of Economics and Financial Issues, 2018)
Using annual data collected between 1994 and 2014, this current study investigate the long-run and short-run cointegration relations between education and economic growth in South Africa using the bounds approach to ARDL model. Our empirical results obtained in the study point to an insignificant relationship between education and economic growth in South Africa, a finding which goes contrary to both existing theoretical and empirical postulations. These obtained results hence imply that the issue with education may not so much with the quantity of existing education but rather the quality. Therefore, our study advises policymakers to place much emphasis on quality of education is such education is likely to promote economic growth. Keywords: Education; economic growth; ARDL model; cointegration, South Africa. JEL Classifications: C32; C51; I25; O40.